Observed Equatorward Propagation and Chimney Effect of Near-Inertial Waves in the Midlatitude Ocean - Yu, Xiaolong; Naveira Garabato, Alberto C.; Vic, Clément; Gula, Jonathan; Savage, Anna C.; Wang, Jinbo; Waterhouse, Amy F.; Mackinnon, Jennifer A. (Geophysical Research Letters, 2022)
International audience The propagation characteristics of near-inertial waves (NIWs) and how mesoscale and submesoscale processes affect the waves' vertical penetration are investigated using observations from a mooring array located in the northeast Atlantic. The year-long observations show that near-inertial motions are mainly generated by local wind forcing, and that they radiate equatorward and downward following several strong wind events (wind stress ≳0.5 N m −2 ). Observational estimates of horizontal group speed typically exceed those of vertical group speed by two orders of magnitude, consistent with predictions from the dispersion relation. Enhanced near-inertial kinetic energy and vertical shear are found only in mesoscale anticyclones with Rossby number of O(0.1). By contrast, submesoscale motions with order one Rossby number have little effect on the trapping and vertical penetration of NIWs, due to their smaller horizontal scales, shorter time scales, and confined vertical extent compared to mesoscale eddies.